2019
DOI: 10.1038/s41598-019-52586-8
|View full text |Cite
|
Sign up to set email alerts
|

Declining maerl vitality and habitat complexity across a dredging gradient: Insights from in situ sediment profile imagery (SPI)

Abstract: Maerl beds form complex biogenic benthic habitats, characterized by high productivity as well as diverse biological communities. Disturbances associated with extraction and/or fishing activities using mobile bottom-contacting gears such as clam-dredges induce the most severe and long-term effects on these fragile habitats. We here investigated the effects of dredge-fishing on maerl in the bay of Brest (France). We quantified maerl beds structure and vitality across a fine scale quantified dredging intensity gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 51 publications
0
27
1
Order By: Relevance
“…Despite their ecological, conservational and evolutionary importance, refugia are currently under great local stress by intense bottom trawling, reaching up to ∼140,000 days, annually. Such localized and intense disturbances, acting in synergy with ongoing and projected climate changes, are likely to compromise the fate of the whole biome and its associated communities, since long lasting or irreversible impacts have already been observed in previously dredged regions, on the scale of years post-dredging (Hall-Spencer and Moore, 2000;Bernard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their ecological, conservational and evolutionary importance, refugia are currently under great local stress by intense bottom trawling, reaching up to ∼140,000 days, annually. Such localized and intense disturbances, acting in synergy with ongoing and projected climate changes, are likely to compromise the fate of the whole biome and its associated communities, since long lasting or irreversible impacts have already been observed in previously dredged regions, on the scale of years post-dredging (Hall-Spencer and Moore, 2000;Bernard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rhodolith refugia are under great local threat from intensive bottom trawling (∼79,000-114,000 days annually), requiring urgent conservation management measures and regulation of this activity. Bottom trawling causes massive mortality of rhodoliths and their associated organisms, as it crushes, buries and eliminates any natural bottom features, while the plume of sediments lifted by trawling reduces light availability, blocks photosynthesis and contributes to additional losses of nearby, non-trawled rhodoliths (Hall-Spencer and Moore, 2000;Thrush and Dayton, 2002;Steller et al, 2003;Wilson et al, 2004;Gabara et al, 2018;Bernard et al, 2019). Such profound impacts are mostly irreversible and damages can still be observed for years post-trawling (Hall-Spencer and Moore, 2000; but see Barberá et al, 2017;Ordines et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fragmentation of large individuals into smaller individuals can therefore result in the loss of structural complexity (Hall‐Spencer and Moore 2000), which in turn reduces overall photosynthetic rates (Bernard et al. 2019) and removes interstitial spaces that support microinvertebrates and trap detritus. Here, we define "microhabitats" as different parts of the rhodolith thalli that are associated with their interior and exterior branches, and their interbranch spaces.…”
Section: Figmentioning
confidence: 99%
“…Studies have shown that structural damage to rhodolith beds can result in significantly reduced richness of invertebrates, and reduced abundance of macroalgae, invertebrates and fish, with implications for other mobile marine species that make use of the secondary productivity associated with rhodoliths (e.g., Gabara et al, 2018;Tompkins & Steller, 2016). Bernard et al (2019) found that substratum compaction, increased rhodolith mortality and decreasing habitat complexity occurred across a gradient of increasing dredging intensity.…”
mentioning
confidence: 99%